educational researcher role in their pedagogical task (Revista Electrónica REDINE, 2018)
Education as a social, human, thoughtful and comprehensive process in different emotional, physical, spiritual and intellectual areas of the student involves conceptual aspects (knowledge), procedural (do), attitudinal (be) and participation (live), by analogy, the role that we fulfill as mediators teachers in teaching and learning  involved to practice multiple roles within the Venezuelan Educational context, there are various activities implicit with it such as planning, evaluating, guiding and investigate among others, and it is precisely this last function that requires current teachers appropriate of a set of evidential skills in abilities and skills focused in knowing research. The Organic Law of Education (2009) and the Curriculum Design of Bolivarian Education System (2007) emanated by the People's Ministry for Education suggest that teacher must be a leader and promoter of scientific research as a fundamental process to educate. Therefore, it is vital that we consider learning environments as an area where countless experiences emerge from our daily experiences characterized by being dynamic, complex and interpersonal relationships between the characters that make life in educational institutions. Hence, the pedagogical task as social action permanently constructed and imbued with individual perceptions worthy of being studied, known, understood and interpreted, this scenario allows us to approach everyday life to reveal the reality from the own voices of social actors. Finally, the transcendental function of venezuelan universities as a space for training in scientific and developmentresearch, rooted in the consolidation of paradigmatic, epistemological and methodological axes that allow us to consolidate our heuristic ability to develop the science of discovery based on a thought, critical, creative and innovative, with the intention to appropriate evident problems in educational environments and provide possible solutions to these problems.
Keywords: teaching researcher; pedagogical task